(De)Gendering Older Patients: Exploring Views on Aging and Older Patients in Romanian General Practitioners - Craciun, Catrinel (2016)
Abstract. Purpose: Demographic changes make it necessary to improve communication with older patients and design gender sensitive health promotion. The present article aimed to explore how general practitioners see old age and what role gender may play in their representations of aging. It also looked whether the gender of the older patients played a role for how general practitioners treated them. Methods: Episodic interviews were conducted with 17 women and 17 men who worked as general practitioners in Romania. Thematic coding was used to analyze data. Results: Findings showed that general practitioners saw old age as negative no matter their gender. Older patients were perceived as difficult and mostly older women were given as negative examples to illustrate treatment non-adherence and psychological or social problems related to aging. Conclusion: Negative aging views combined with a (de)gendering of aging patients may lead to maintain negative aging stereotypes and gender inequality in old age. Implications for preventing this from happening are discussed